1993
DOI: 10.1037/0278-7393.19.4.952
|View full text |Cite
|
Sign up to set email alerts
|

Intuitive physics in action and judgment: The development of knowledge about projectile motion.

Abstract: This article contrasts intuitive knowledge about projectile motion expressed in action with knowledge expressed in explicit judgments. In the action condition of Experiment 1 children and adults threw a ball horizontally from different heights to hit targets on the floor; in the judgment condition the same subjects rated the respective launch speeds required. All age groups appropriately varied the launch speed with respect to both height of release and target distance in the action condition. In the judgment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
102
1
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(110 citation statements)
references
References 72 publications
3
102
1
2
Order By: Relevance
“…For instance, Hubbard suggests that implicit knowledge reflects internalization of invariant physical principles, whereas explicit knowledge about motion may be less accurate. Similarly, Krist et al (1993) suggested that perceptually based knowledge is more accurate than verbal concepts of motion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Hubbard suggests that implicit knowledge reflects internalization of invariant physical principles, whereas explicit knowledge about motion may be less accurate. Similarly, Krist et al (1993) suggested that perceptually based knowledge is more accurate than verbal concepts of motion.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that from daily interactions with moving objects, people develop perceptually based knowledge about motion that is much more accurate than their naive verbal-cognitive concepts of motion and that this implicit knowledge follows a different developmental course (e.g., Krist, Fieberg, & Wilkening, 1993). Similarly, Freyd (1987) originally suggested that our implicit intuitive knowledge about motion, as measured in RM studies, reflects internalization of physical principles.…”
mentioning
confidence: 99%
“…For situations where it is reasonable to suppose that beliefs can influence imagery, a useful method for verifying the presence of imagery is to show that people do not have beliefs that could fully imitate imagery outcomes (e.g., Finke, 1985;Kosslyn, 1980). Krist, Fieberg, and Wilkening (1993), for example, showed that 5-year-olds do not correctly answer questions about where an object will land if it is pushed off a ledge. Children believe that the higher an object's release point, the faster it must be pushed to reach a given target.…”
Section: A Task For Investigating Physical Imagerymentioning
confidence: 99%
“…Implicit learning has been seen as responsible for at least some aspects of first-language (e.g., Chandler, 1993) and second-language learning (e.g., Carr & Curran, 1994), category elaboration, reading and writing acquisition, adaptation to the physical constraints of the world (e.g., Krist, Fieberg, & Wilkening, 1993), and acquisition of social skills (Reber, 1993). Most of this learning takes place during infancy and childhood and constitutes the essential core of what a newborn must acquire to become an adult.…”
Section: Implicit Learning Processes In Developmentmentioning
confidence: 99%